Training in Integrated Coconut Product Processing and Marketing with the Implementation of Zero Waste in Banjar Lantangidung, Sukawati, Gianyar, Bali - Setianingsih, Ni Luh Putu Putri; Sudiarta, I Wayan; Rustini, Ni Made; Padmarini, Ni Made Andira; Patni, Gusti Ayu Yunda Darma; Mulia, I Komang Oki Budi (Asian Journal of Community Services, 2024)
Processing and marketing of integrated coconut products with the implementation of zero waste will be carried out by PKK Br. Lantangidung, Batuan Sukawati, Gianyar Bali. The goal achieved is to provide appropriate technology for processing coconut, which has the potential to be found in Batuan Village, Sukawati Virgin Coconut Oil (VCO), Serundeng (saur), and by-products, namely activated charcoal for health and consumption. The methods that will be used in implementing this training are interviews, face-to-face, counseling, and direct practice. The output target to be achieved is that training participants can independently make processed products and understand entrepreneurial knowledge and marketing management so that they can become economically independent